Business transformation : a roadmap for maximizing organizational insights - Zeid, Aiman (Hoboken, New Jersey : Wiley, 2014)
"Effectively introduce and promote analytics within your enterprise. All companies use information to set strategies and accomplish business objectives. But how many CEOs and CIOs would say they are satisfied that their companies get maximum value from information? The Data Advantage reveals how SAS's Information Evolution Model (IEM) can be used together with analytics for groundbreaking results. Author Aiman Zeid provides the necessary information you need to introduce and promote the use of analytics and insight across your organization. Along with examples and best practices of global companies that have successfully been through this process, you'll learn how to identify the starting point and develop a road map for execution. Reveals how to introduce and promote the use of analytics and insights across your organization Written by a lead developer at SAS global Business Intelligence Competency Center program and services Features global case studies and examples Practical and insightful, this reference provides businesses with an essential blueprint for creating improvements that optimize business returns and put the potential of data analytics to work"--
Business Transformation: A Roadmap for Maximizing Organizational Insights; Copyright; Contents; Foreword; So What Has Changed?; Putting the Spotlight on People and Culture; And Some Things Stay the Same . . .; Notes; Preface; Acknowledgments; Chapter 1: The Critical Role of Business Insight; The Disruptive Nature of Data; An Unconventional Look at Conventional Wisdom; Innovating at the Speed of Data; Weighing Risk and Bringing the Better Part of Gut Instinct Back into the Equation; People, Process, Technology, and Culture; Starting the Journey; Notes Chapter 2: The Journey: Taking the First Steps toward Transforming Your Organization Different Approaches; Juggling Multiple Challenges; How to Deal with Challenges Effectively; Executive Sponsorship: Critical to Success; Understanding Current Capabilities; Aligning Capabilities with Business Objectives; Let's Start the Journey; Taking the First Steps to Transforming Your Organization; Note; Chapter 3: Challenged Organizations: When Rugged Individualism and Department Silos Aren't Enough; Getting Along One Day at a Time: Organizations at the Individual Level; Decisions after the Fact Rogues Manning the Spreadsheets When "Have It Your Way" Isn't a Good Thing; Superhighways and Dirt Roads; A Little Too Much Rugged Individualism; Consolidated, but Not Cohesive: Organizations at the Departmental Level; Subject Matter Experts and Gatekeepers; Strong Interior, Weak Exterior; Many Roads, Not Enough Bridges; "Us versus Them"; Understanding the True Consequences of the Challenged Levels; Business Transformation Strategy Objectives for Challenged Organizations; Notes; Chapter 4: Foundational Organizations: Making the Leap to an Enterprise-Wide Approach The Possibilities That Come with Patience Seeing the Value Across the Enterprise; How an Enterprise Level Organization Functions; Knowledge Workers Equipped with the Right Information and Technologies; No More KPI Confusion; Freedom of Choice Knitted into a Sound Framework; All for One, One for All; Big Data: The Big Opportunity for Enterprise Level Organizations; Don't Let Up; Continuous Improvement Required; Business Transformation Strategy Objectives for Foundational Organizations Chapter 5: Progressive Organizations: Harnessing the Power of Information to Achieve Market Advantage and Expand Their Business Offerings Optimization: The Easiest Business Case of All; Self-Managing Knowledge Workers; Feeding the Continuous Improvement Loop; Anywhere, Anytime Intelligence; Thriving on Change; Getting the Most from Optimization; Toward Innovation and Beyond; Creative Collaborators; Managing Constant Renewal; Growing a Support Network for Innovation; A Culture of Entrepreneurial Innovation; Stopping at the Optimized Level-Or Striving toward the Innovate Level.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Organizational behavior; Organizational change; Business planning; COMPUTERS -- Enterprise Applications -- Business Intelligence Tools; BUSINESS & ECONOMICS -- Marketing -- Research; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; Business planning; Information technology -- Management; Organizational behavior; Organizational change; Electronic books